Design gas turbine vane with ceramics matrix composites - Law, Xuecheng (Nanyang Technological University, 2020)
To improve the efficiency of a gas turbine engine (GTE), there is a need to develop new technologies to increase the turbine inlet temperature. One promising technology is to replace the current Ni-based superalloys material with Ceramic Matrix Composite (CMC). The CMC material can operate 200℃ hotter with a potential of 6% improvement in fuel efficiency. However, due to the nature of CMC material and its unique manufacturing process, it is difficult to use this material to manufacture a complex engine part. This research focus on overcoming the limitation of the CMC manufacturing process to design the Nozzle Guide Vane (NGV) of the engine by splitting this single complex part into multiple simpler sub-components. The novel NGV design would consist of multiple sub-components including turbine vane airfoil and multiple platforms. To substantiate the design, thermal and structural analysis would be performed. Comparisons are made using basic model of NGV Model 1 with 6 NGV novel models. NGV Model 7 results in peak principal stresses of lower than 20% of SiC/SiC yield strength and 40% reduction from the NGV Model 1 (baseline). Next, the platform is designed to minimise air leakages in NGV. The result indicates that the peak principal stresses for selected Model 4 is around 50% of SiC/SiC yield strength. Additionally, 6 turbine case models are designed for the newly proposed NGV designs to accommodate the platform and NGV. As part of the project, a prototype is fabricated with fiber glass fabric laminate as an alternating material due to its similar hardness and brittle characteristics with CMC. To aid with the fabrication, 3D printed molds are created. Simplified composite vacuum bagging method is used to cure the fiber glass laminate over the 3D printed molds. The prototype of all these components are assembled to show the compatibility and feasibility of the CMC design. In conclusion, this research supported by analysis and prototype, shows the potential of using Ceramics Matrix Composites (CMC) to design the Nozzle Guide Vane (NGV) of a Gas Turbine Engine.